Effects of fibrin sealant and bone fragments on defect regeneration performed on rat tibiae: An experimental study - Barbosa de Oliveira, Carla Teresa (2020)
Fibrin sealant (FS) is a biomaterial that exhibits hemostatic and repairing properties. It has been successfully used as scaffolds and adhesives to improve repair and regeneration of tissues. The objective of this study was to evaluate the effect of FS in the regeneration process of bone defects in male rat tibias through macroscopic, microscopic and mechanical analysis. A bone defect of 2.9 mm was performed on the medial face of the proximal third of the tibia of 40 rats and implanted FS and autologous bone graft (AG). The animals were divided into four groups: animals with bone defect without any treatment (CON), animals treated with fibrin sealant (TFS), animals treated with autologous graft (TAG) and animals treated with fibrin sealant and autologous graft (FSAG). The animals were euthanized 42 days after surgery. Macroscopic analysis showed no difference between the groups (p > 0.05) in relation to tibial weight, but a statistically significant difference (p = 0.005) was observed for their length. Micro-computed tomography (micro-CT) revealed tendentious values regarding bone microarchitecture and FS. Bone mineral densitometry (BMD) showed significance between the FSAG (p = 0.009) and TFS (p = 0.007) groups. The bone mineral content (BMC) presented a significant difference between all groups (p = 0.020). Maximum strength showed a significant difference between the FSAG group (p = 0.007) and the others. The results obtained in relation to the relative stiffness also present a significant difference (p = 0.023). Newly formed bone showed significant differences between groups (p = 0.035). We conclude that bone defect regeneration was directly influenced by the use of FS and AG.